Partnership in Practice Research: a Norwegian Experience - Jan Fook; A. Johannessen; M. Psoinos (Social Work & Society, 2011)
Acknowledgement to Helen Pain This article outlines some of the issues involved in developing partnerships between service users, practitioners and researchers. It discusses these through some experience in Oslo as part of a national level agreement (HUSK) to improve social services in Norway through research and knowledge development. It begins with a review of the main concepts and debates involved in developing collaborative partnerships for practice-based research, particularly in the social services arena. The HUSK program is then described. The article then traces some specific developments and challenges in negotiating partnership relations as discussed by program participants (users, practitioners and researchers) in a series of workshops designed to elicit the issues directly from their experience.